The Application Of The Jarimatika Method Through Singing Media To Improve Mathematics Learning Outcomes - Rahmi K; Sri Hastati; Rahmawati Rahmawati (ALENA : Journal of Elementary Education, 2026)
This study aims to describe and analyze the application of the Jarimatika method through singing media in improving teacher activities, student activities, and mathematics learning outcomes in multiplication operation material for grade II STUDENTS MIS DDI Hasanuddin Maros Regency. The research uses the Classroom Action Research (PTK) approach with the Kurt Lewin model which consists of four stages, namely planning, implementation of actions, observation, and reflection. The research was carried out in two cycles with 13 students consisting of five male students and eight female students. Data collection techniques include observation, tests, and documentation, while data analysis is carried out descriptively, quantitatively, and qualitatively. The results of the study show that the application of the Jarimatika method through singing media is able to improve the quality of the process and results of mathematics learning. Teacher activity increased from 72.1% in Cycle I to 86.1% in Cycle II. Student activity increased from 75% to 83%. Students' learning outcomes have also increased, as shown by the percentage of learning completeness from 46% in Cycle I to 77% in Cycle II. This improvement shows that the use of the Jarimatika method through singing media is able to create more active, fun, and developmental learning in accordance with the developmental characteristics of elementary school students so as to help students understand the concept of multiplication more easily. Based on the results of the study, it can be concluded that the application of the Jarimatika method through singing media is effective in increasing teacher activities, student activities, and mathematics learning outcomes of multiplication operation material in grade II STUDENTS MIS DDI Hasanuddin Maros Regency. This method can be used as an alternative to learning mathematics in elementary school, especially in the material on multiplication calculation operations.